The Influence of the Pancasila and Rahmatan lil-Alamin Student Profile Reinforcement Project (P5RA) on Tolerance Attitudes among Madrasah Aliyah Students - Moch Umar Safari; Ainol Ainol; Herwati Herwati (STAI Syaichona Moh. Cholil Bangkalan, 2025)
This study aims to determine the effect of the Pancasila and Rahmatan lil-Alamin (P5RA) Student Profile Strengthening Project on the formation of students' tolerance attitudes in the Madrasah Aliyah environment. P5RA is an integral part of the Merdeka Curriculum implemented in madrasas, with the main objective of instilling character values, including attitudes of tolerance between religious communities and social diversity. This study uses a correlational quantitative approach with data collection techniques through a Google Form-based questionnaire distributed to 124 grade XI students at MA Negeri 2 Probolinggo. The research instrument consisted of 24 statement items for variable X and 10 items for variable Y that had been tested for validity and reliability. Data analysis used Pearson correlation and simple linear regression. The results showed that there was a very strong relationship between the implementation of P5RA and students' tolerance attitude with a correlation value of 0.84. The coefficient of determination of 69.88% indicates that most of the variation in students' tolerance attitude is influenced by the implementation of P5RA. The regression equation obtained is Y = 0.41X + 0.88, which indicates that an increase in P5RA implementation will have a positive impact on increasing students' tolerance attitudes. This study concludes that P5RA has a significant role in shaping students' tolerant character. The implications of the results of this study reinforce the importance of integrating the values of religious moderation and tolerance in every aspect of learning and school activities. Recommendations are given to madrasah and policy makers to continue to develop the P5RA program thoroughly and sustainably.